Penerapan Metode POGIL Pada Materi Konsep Mol Di Kelas X IPA SMA Negeri 2 Langowan - Gloria Viarosa Manampiring; Ignatius Santoso; Ardi Kapahang (Oxygenius Journal Of Chemistry Education, 2019)
The purpose of this study was to determine the application of the POGIL method to the learning outcomes of Grade X Science students on the mole concept material.This research was implemented in class X IPA 1 and X IPA 2 SMA Negeri 2 Langowan school year 2018/2019. The method used is experimental method with post – test only control design research. In this study applied different methods on 2 classes namely POGIL class and lecture class with the number of students of each class of 23 students. Student learning Data is derived from the post-test value. Data analysis uses test-T with a significant level of α = 0.05. Analysis of student learning statistics test results obtained the value T > T table or 4.31 > 1.68. So that the H1 can be concluded accepted and H0 rejected, this shows that students ' learning outcomes with the application of the POGIL method are greater than the student learning outcomes by the lecture method on the concept of Mole material.